Clinical Manifestations - Newton, Coco; Cepukaityte, Giedre; Chan, Dennis (Alzheimer's & dementia, 2023)
Increasing evidence suggests that impairments of spatial navigation, orientation and memory may represent one of the earliest features Alzheimer's disease (AD), preceding deficits in other cognitive domains. This is consistent with early pathological tau and amyloid deposition in temporal and parietal brain regions implicated in spatial processing. However, it remains unclear which metrics and spatial behaviours can i) differentiate high-risk, preclinical or prodromal AD individuals, and ii) may be captured with digital devices suitable for future deployment at scale in clinical practice. We addressed this knowledge gap with a systematic review. Two databases (PubMed/Web of Science) were searched following PRISMA guidelines. Medical subheading keywords for different dementia types were combined with prodromal, preclinical and genetic or disorder risk factor terms. We included studies published until October 2022 that collected digital or physical objective measures of egocentric or allocentric processing (wayfinding, orientation, reference frame translation, route learning or path integration). We excluded diagnoses of other conditions or dementia, cross-sectional MCI studies without biomarkers, young adults, case studies, interventional studies or studies without appropriate controls. 25 articles were included from 316 identified abstracts. None investigated non-AD dementias. 131 metrics were extracted from 38 different tasks, of which 31 where digital (81%). 82 metrics showed differentiation of predementia AD groups (63%). We harmonised these into 21 distinct summary metrics covering four domains of active or passively tracked spatial behaviours. Across all domains, metrics capturing decreased navigation efficiency (i.e. distance or time required to find goals) and accuracy (i.e. distance or angle from goal) were most frequently reported, but egocentric better differentiated prodromal than preclinical groups. Metrics for path integration and passive tracking of everyday GPS data were promising but relatively under-explored. For future clinical use, spatial tests will require standardisation and validation against established markers of disease. These review data will inform the selection of digital tools to assess spatial behaviours in at-risk, preclinical and prodromal AD populations as part of the EDoN Initiative.